Nanoscale Ruthenium-Containing Deposits from Ru(CO)4I2via Simultaneous Focused Electron Beam-Induced Deposition and Etching in Ultrahigh Vacuum: Mask Repair in Extreme Ultraviolet Lithography and beyond - Bilgilisoy, Elif; Yu, Jo Chi; Preischl, Christian; McElwee-White, Lisa; Steinrück, Hans-Peter; Marbach, Hubertus (ACS Applied Nano Materials, 2021)
The deposition of nanoscaled structures with a desired shape on the intended position of the substrate material is crucial for nanomaterial applications. Electron beam-induced deposition with a highly focused beam enables achievement of high accuracy and precision in this respect. Hence, we investigated the focused-electron-beam-induced deposition of Ru-containing deposits on SiO2 and sputter-cleaned silicon in ultrahigh vacuum to achieve comparably clean and morphologically well-defined Ru nanomaterials, which is relevant especially in the field of mask repair for extreme ultraviolet lithography. The precursor Ru(CO)4I2 was held at 340-345 K, and the applied electron doses were varied from 1.56 to 9.36 C/cm2 using a focused electron beam (5 keV, 1.5 nA, and 10 nm diameter). Local Auger electron spectroscopy along with subsequent sophisticated fitting procedures not only revealed the elemental composition but also enabled determination of the thickness of the fabricated deposits. Ru contents of up to 56% can be achieved at lower electron doses; at higher doses, the Ru content decreases to 45% and simultaneously the content increases. The initially lower I content is attributed to simultaneous focused electron beam-induced etching, which is found to be competing with the deposition process. The etching is evidenced by atomic force microscopy, where the structures are observed to have negative apparent height for low electron doses. With increasing electron doses, the deposits exhibit positive apparent heights because the etching is less pronounced at higher electron doses, once the Ru surface coverage has increased. The high Ru content and difficult balance between electron-induced deposition and etching considerably expand the possibilities of engineering nanostructured materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Auger electron spectroscopy (AES); focused electron beam-induced deposition (FEBID); focused electron beam-induced etching (FEBIE); ruthenium nanomaterials; scanning electron microscopy (SEM)